Sigma‐1 receptor activation‐induced glycolytic ATP production and endothelial barrier enhancement. (26th April 2020) - Motawe, Zeinab Y.; Farsaei, Forouzandeh; Abdelmaboud, Salma S.; Cuevas, Javier; Breslin, Jerome W.
Abstract: Objective: We tested the hypothesis that σ1 modulates endothelial barrier function due to its influence on endothelial bioenergetics. Methods: Cultured HUVEC monolayers were used to model the endothelial barrier. ECIS, Transwell assays, and immunofluorescence labeling of junctional proteins were used to evaluate endothelial barrier function. Endothelial cell bioenergetics was determined using extracellular flux analysis and direct ATP level measurements. The endothelial‐specific contribution of σ1 was tested using the σ1‐selective agonist, PRE‐084, and with targeted knockdown of σ1 expression using siRNA. Results: Activation of σ1 with PRE‐084 significantly enhanced endothelial barrier function and decreased permeability to albumin and dextran. Knockdown of σ1 with siRNA reduced barrier function and abolished PRE‐084‐induced endothelial barrier enhancement. PRE‐084 upregulated endothelial glycolysis and glycolytic ATP production, but this response was abolished by siRNA‐mediated knockdown of σ1 expression. PRE‐084 also reduced the degree of endothelial barrier dysfunction caused by the mitochondrial oxidative phosphorylation uncoupler CCCP. Conclusion: Activation of σ1 enhances endothelial barrier function and modulates the ratio of glycolytic versus mitochondrial ATP production. These novel findings suggest that endothelial σ1 may prove beneficial as a novel therapeutic target for reducing microvascular hyperpermeability and counteracting mitochondrial dysfunction.